Human capital: A foundation for achieving organizational excellence - Mimoune, Mohamed; Chenna, Djamal; Madjene, Mohamed Mahfoudh (International journal of economic perspectives, 2025)
This study aims to highlight human capital as one of the most critical strategic resources for organizations and a cornerstone of their success and institutional excellence. The significance of this resource has grown remarkably in recent decades, particularly with the paradigm shift in perceiving human elements—from being reduced to mere physical labor within traditional production frameworks to becoming an exceptional asset capable of driving innovative and competitive transformations. Human capital no longer confines itself to conventional roles; instead, it has emerged as a primary source of value creation and a fundamental determinant for acquiring competitive advantages that align with organizational goals in dynamic work environments. The study demonstrates how the focus on human capital has evolved from a narrow conceptualization to a comprehensive vision centered on investing in skill and knowledge development. It establishes an organic linkage between human capital and institutional excellence across domains such as technological innovation, product development, and global market competitiveness. Furthermore, the study underscores that organizational survival and superiority hinge on the proactive utilization of this resource, whether through fostering a creativity-driven organizational culture or adopting effective strategies for knowledge management and talent retention.